The economic value of INTUITY in aortic valve replacement. (2nd October 2016) - Moore, Matthew; Barnhart, Glenn R.; Chitwood, Walter Randolph; Rizzo, John A.; Gunnarsson, Candace; Palli, Swetha R.; Grossi, Eugene A.
Abstract: Objective: The recent development of the EDWARDS INTUITY Elite™ (EIE) valve system enables the rapid deployment of a prosthetic surgical heart valve in an aortic valve replacement (AVR) procedure via both the minimally invasive (MISAVR) and conventional (CAVR) approaches. In order to understand its economic value, this study performed a cost evaluation of the EIE valve system used in a MIS rapid-deployment approach (MIS-RDAVR) vs MISAVR and CAVR, respectively, compared to standard prosthetic aortic valves. Methods: A simulation model was developed using TreeAge (and validated with MS Excel) to compare the inpatient utilization and complication costs for each treatment arm. Thirty-day clinical end-points for the MIS-RDAVR (mortality and complications) were taken from the TRANSFORM trial; and a best evidence review of the published literature was used for the MISAVR and CAVR approaches. Studies were pooled and parameter estimates were weighted by sample size in order to compare the TRANSFORM patients. Cost data (2016 USD) were taken from the Premier database. Incremental cost and cost-effectiveness was assessed and one-way/probabilistic sensitivity analyses performed to gauge the robustness of the results. Results: MIS-RDAVR costs 2, 621 less than CAVR and had lower mortality rates, making it a superior (dominant) technology relative to CAVR. MIS-RDAVR costs 4, 560 more than MISAVR, but was associated with an additional 0.20 life years-per-patient. This implies a cost-effectiveness ratio of 22, 903 per-life-year-gained. Thus, MIS-RDAVR is cost-effective compared to MISAVR. Conclusions: The EIE valve system deployed in a MIS approach appears to be a cost-effective technology compared to MISAVR and CAVR. When compared to CAVR it may achieve cost savings as well. These results suggest that MIS-RDAVR confers superior economic value compared to both standard MISAVR and CAVR via lowered key complication rates (re-operation, renal complications, wound infection, TIA, endocarditis) and utilization (cross-clamp time, hospital ward days).